Polychlorinated Biphenyls, Cyanotoxins, and Trace Elements in Commercial Fish Species from a Freshwater Protected Area: Co-occurrence in Pertusillo Lake, Southern Italy - Pace, Rita De; Storelli, Maria Maddalena; Barone, Grazia; Messineo, Valentina; Bruno, Milena (Geography, Earth Science and Environment: Research Highlights Vol. 4, 2025)
Studies have shown the presence of anthropic contaminants in inland waters of various continents, as found in lakes polluted by industries. This study investigates the simultaneous presence of Polychlorinated Biphenyls, Cyanotoxins, and Trace Elements in ichthyic fauna from Lake Pertusillo. A total of 79 fish samples representing nine species were collected from Pertusillo Lake, a Site of Community Importance (SCI) located in Southern Italy. This freshwater reservoir, intended for drinking water, is situated in an area also used for drilling activities. The presence of microcystins (MYCs) and cylindrospermopsins (CYLs) was assessed using ELISA assays, with 86% of total fish tissue samples positive for MYC presence, at concentration values ranging from a minimum of 0.19 ng/g to a maximum of 2.01 ng/g b.w. (body weight) and 64% of samples positive for CYN, with maximum concentrations at 0.78 ng/g in muscle tissue. Additionally, 10 fish samples were analyzed for trace elements via atomic absorption spectrophotometry and polychlorinated biphenyls (PCBs) using GC-MS in EI mode. The findings revealed the co-occurrence of significant cyanotoxins and industrial pollutants in the fish. Further research is necessary to assess the combined effects of these contaminants on the lake’s ecosystem and fish population, and to develop a comprehensive risk assessment for the human population in the surrounding region.